Carfilzomib-lenalidomide-dexamethasone vs lenalidomide-dexamethasone in relapsed multiple myeloma by previous treatment - Dimopoulos, M A; Stewart, A K; Masszi, T; Špička, I; Oriol, A; Hájek, R; Rosiñol, L; Siegel, D; Mihaylov, G G; Goranova-Marinova, V; Rajnics, P; Suvorov, A; et al. (Blood cancer journal, 2017)
Carfilzomib, a proteasome inhibitor, is approved as monotherapy and in combination with dexamethasone or lenalidomide-dexamethasone (Rd) for relapsed or refractory multiple myeloma. The approval of carfilzomib-lenalidomide-dexamethasone (KRd) was based on results from the randomized, phase 3 study ASPIRE (NCT01080391), which showed KRd significantly improved progression-free survival (PFS) vs Rd (median 26.3 vs 17.6 months; hazard ratio (HR)=0.690; P=0.0001). This subgroup analysis of ASPIRE evaluated KRd vs Rd by number of previous lines of therapy and previous exposure to bortezomib, thalidomide or lenalidomide. Treatment with KRd led to a 12-month improvement in median PFS vs Rd after first relapse (HR 0.713) and a 9-month improvement after ⩾2 previous lines of therapy (HR 0.720). Treatment with KRd led to an approximate 8-month improvement vs Rd in median PFS in bortezomib-exposed patients (HR 0.699), a 15-month improvement in thalidomide-exposed patients (HR 0.587) and a 5-month improvement in lenalidomide-exposed patients (HR 0.796). Objective response and complete response or better rates were higher with KRd vs Rd, irrespective of previous treatment. KRd had a favorable benefit-risk profile and should be considered an appropriate treatment option for patients with 1 or ⩾2 previous lines of therapy and those previously exposed to bortezomib, thalidomide or lenalidomide.
Keywords: senioři; Thalidomide; Treatment Outcome; Oligopeptides; senioři nad 80 let; Multiple Myeloma; thalidomid; výsledek terapie; Middle Aged; mužské pohlaví; oligopeptidy; Neoplasm Recurrence, Local; Adult; lokální recidiva nádoru; Lenalidomide; Aged, 80 and over; mnohočetný myelom; Disease-Free Survival; ženské pohlaví; Humans; dexamethason; lidé středního věku; Antineoplastic Combined Chemotherapy Protocols; protokoly protinádorové kombinované chemoterapie; Dexamethasone; dospělí; Female; Aged; lenalidomid; přežití bez známek nemoci; lidé; Male